Persepsi Masyarakat terhadap Usaha Anyaman Enceng Gondok Di Desa Banyu Hirang Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara - Miranda Romaully Br. Sitanggang; Juwairiah Juwairiah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to determine the public perception of the positive and negative effects of water hyacinth woven business in Banyu Hirang Village, South Amuntai District, Hulu Sungai Utara District. This study uses data collection using a questionnaire (questionnaire). The public perception clearly shows that the positive impact of the average community score is 59.8 and from the craftsmen community 63.3 in total for both get an average of 61.55 on the continuum line in the area strongly agree, which means that perception The community has a positive impact on the economic, social, cultural and environmental aspects of the water hyacinth webbing business, which has a very positive impact on the community. Whereas the negative impact of the average score of the general community is 53.3 and that of the craftsmen community is 49.2 in total for both the average 51.25 on the continuum line in the agreed area which means that the community's perception of the negative impact on the business water hyacinth webbing seen in terms of economic, social, cultural and environmental aspects is a negative impact on society